DAESI Facilitator’s Opinion on Input Dealers as Para-extension Agents: A Q-sort Method - Gopichand, Balusu; Shirur, Mahantesh; Kumar, G. Naveen (Journal of Agricultural Extension Management, 2024)
The need for input dealers as para-extension professionals is more evident from the pressure the public extension system face in delivering advisory services and implementing agriculture development and farmers welfare programs. The DAESI program is particularly designed to improve the knowledge and skills of the input dealers to provide quality extension services. The facilitators who plans the program and implement it at the NTI level are always keen on observing the input dealers. The facilitator’s opinion is most important in this regard to investigate the most agreeable extension services delivered by input dealers and the vice-versa. The Q-sort method was employed to know the opinion where the facilitaors are forced to choose the specified number of agreed, neutral and disgareed activities.